Influence of metallic molar ratio on the electron spin resonance and thermal diffusivity of Zn-Al layered double hydroxide - Ali Ahmed, Abdullah Ahmed; Talib, Zainal Abidin; Hussein, Mohd Zobir (Hindawi Publishing Corporation, 2013)
The coprecipitation method was used to prepare Zn-Al layered double hydroxide (Zn-Al-NO3-LDH) at pH 7.5 and different Zn 2+/Al3+ molar ratios of 2, 3, 4, 5, and 6. The elemental, structural, and textural properties of prepared samples were studied. The crystallinity of prepared LDH nanostructure decreases as Zn2+/Al 3+ molar ratio increases. The electron spin resonance (ESR) spectroscopy of different LDH samples showed new ESR spectra. These spectra were produced due to the presence of different phases with formed LDH such as ZnO phase and ZnAl2O4 spinel. At low Zn2+/Al 3+ molar ratio, the ESR signals were produced from the presence of free nitrate anions in the LDH interlayer. Above Zn2+/Al3+ = 2, the ESR signals were attributed to the existence of ZnO phase and ZnAl2O4 spinel in the samples. Because the nuclear magnetic moment of 67Zn is lower than 27Al, the increasing in Zn2+/Al3+ molar ratio causes a reduction of the magnetic activity of ZnAl2O4 spinel. Thermal diffusivity versus in situ temperature showed nonlinear relation for different samples due to the changing in the water content of LDH as temperature increases. The dc conductivity of samples decreased as Zn2+/Al3+ molar ratio.